2006
DOI: 10.1007/s10495-005-3346-1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular effects of protons: Apoptosis induction and potential implications for cancer therapy

Abstract: Due to their ballistic precision, apoptosis induction by protons could be a strategy to specifically eliminate neoplastic cells. To characterize the cellular and molecular effects of these hadrons, we performed dose-response and time-course experiments by exposing different cell lines (PC3, Ca301D, MCF7) to increasing doses of protons and examining them with FACS, RT-PCR, and electron spin resonance (ESR). Irradiation with a dose of 10 Gy of a 26,7 Mev proton beam altered cell structures such as membranes, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 49 publications
(37 reference statements)
4
56
2
Order By: Relevance
“…A recent report suggests that cell death induced by proton is apoptosis rather necrosis or autophagy (Di Pietro et al, 2006). In our result, cell death by proton is clearly apoptotic, i.e., nuclear DNA fragments and segregating pattern of nucleus shown in Figure 3A.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A recent report suggests that cell death induced by proton is apoptosis rather necrosis or autophagy (Di Pietro et al, 2006). In our result, cell death by proton is clearly apoptotic, i.e., nuclear DNA fragments and segregating pattern of nucleus shown in Figure 3A.…”
Section: Discussionsupporting
confidence: 67%
“…Cell death induced by proton beam is identified as apoptosis (Di Pietro et al, 2006). The study investigated that genes involved in various phases of apoptosis are checked by RT-PCR and used LET instead of SOBP of proton beam.…”
Section: Introductionmentioning
confidence: 99%
“…Bmi-1 -/ -mice are known to have increased levels of ROS and hydroxyl free radicals that are produced by oxidative stress, which subsequently results in an increase in DNA double strand breaks (32). The present results demonstrated that the PQQ-supplemented diet decreased the number of BKO-induced double strand DNA breaks in the liver.…”
Section: Effects Of Pqq On the Ros Levels In The Liver Of Bmi-1supporting
confidence: 58%
“…Apoptosis contributes to tumor growth kinetics and response to radiotherapy, and some radiosensitive tumors have a tendency to undergo apoptosis [14]. There may be differences in the kinetics and extent of apoptosis induction between protons and photon [15,16]. Gerelchuluun et al showed greater induction of in situ DNA double-strand breaks and apoptosis by proton beams in the early phase after irradiation, compared with photon beams.…”
Section: Biological Characteristicsmentioning
confidence: 99%